(untitled) (REMUNOM, 2025)
Soil is an essential resource for agricultural production and fundamental ecological functions. However, inadequate management practices and input use have accelerated its degradation, especially in tropical regions. This article seeks to answer the following questions: What are the main advances in scientific research on soil management and fertility? How have fertilizer composition and the application of acidity correctives been addressed in the literature? Thus, the objective is to investigate the scientific production on the key aspects of soil use, management, and fertility, as well as fertilizer composition and the application of acidity correctives. The methodology adopted was a literature review, considering studies discussing the impact of practices such as liming, gypsum application, and the use of mineral and organic fertilizers. The results demonstrate that the application of acidity correctives, such as limestone and gypsum, improves soil structure, neutralizes acidity, and reduces the presence of toxic elements. Organic fertilizers, on the other hand, enhance water retention, improve microbial activity, and contribute to the sustainability of agricultural systems. It is concluded that technological advancements and traditional practices must be integrated to promote sustainable soil fertility. The need for technical training for farmers and public policies that encourage practices adapted to local conditions is highlighted. Future research should adopt interdisciplinary approaches, exploring the technical, social, and economic aspects of soil conservation.